2020
DOI: 10.1016/j.celrep.2020.107958
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of UHRF1 Regulates Hemi-methylated DNA Binding and Maintenance of Genome-wide DNA Methylation

Abstract: Highlights d Acetylation of UHRF1 is regulated by PCAF and HDAC1 d PCAF-mediated UHRF1 acetylation disrupts its hemimethylated DNA binding d Deacetylation by HDAC1 is required for chromatin association of UHRF1 during S phase d Deregulation of UHRF1 acetylation impedes the inheritance of global DNA methylation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the previous study, we showed that UHRF1 K490 acetylation through PCAF impairs hemi-methylated DNA binding of UHRF1 (Hahm et al 2020 ). To identify whether TIP60-mediated acetylation of UHRF1 could induce any physiological effect on HCT116 cells, we performed MTT assay and colony formation assay with shUHRF1 by comparing transfection of UHRF1 WT and 4KR mutant.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the previous study, we showed that UHRF1 K490 acetylation through PCAF impairs hemi-methylated DNA binding of UHRF1 (Hahm et al 2020 ). To identify whether TIP60-mediated acetylation of UHRF1 could induce any physiological effect on HCT116 cells, we performed MTT assay and colony formation assay with shUHRF1 by comparing transfection of UHRF1 WT and 4KR mutant.…”
Section: Resultsmentioning
confidence: 94%
“…Previously, we identified that UHRF1 is acetylated by PCAF and inhibits its binding to hemi-methylated DNA in HCT116 cell line (Hahm et al 2020 ). Another study revealed that TIP60 acetylated UHRF1 at K659 (isoform 1, K644 at isoform 3) by in vitro acetylation assay (Zhang et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…S6 c). Studies with mouse embryonic stem cells (mESCs) and colorectal cancer cells showed that knockdown of UHRF1 induced global DNA hypomethylation 32 , 53 , 54 . These results suggest the possibility that DNMT1 is predominant DNA methylation regulator in THP-1 cells which has more important roles in regulating global DNA methylation pattern than UHRF1 and DNMT3B.…”
Section: Discussionmentioning
confidence: 99%
“…The acetylation of UHRF1 is crucial for the regulation of hemi-methylated DNA binding and maintenance of genome-wide DNA methylation. The acetylation of UHRF1 is regulated by P300/CBP-associated factor (PCAF) and HDAC1 [ 40 ]. Initially, UHRF1 is acetylated by PCAF at K490, thereby disrupting its binding to the hemi-methylated DNA in the nascent DNA.…”
Section: Ptms Of Uhrf1 Proteinmentioning
confidence: 99%